An ultra scale‐down characterization of low shear stress primary recovery stages to enhance selectivity of fusion protein recovery from its molecular variants. Issue 7 (16th March 2013) - Lau, Eduardo C.; Kong, Simyee; McNulty, Shaun; Entwisle, Claire; Mcilgorm, Ann; Dalton, Kate A.; Hoare, Mike
Abstract Fusion proteins offer the prospect of new therapeutic products with multiple functions. The primary recovery is investigated of a fusion protein consisting of modified E2 protein from hepatitis C virus fused to human IgG1 Fc and expressed in a Chinese hamster ovary (CHO) cell line. Fusion protein products inevitably pose increased challenge in preparation and purification. Of particular concerns are: (i) the impact of shear stress on product integrity and (ii) the presence of product‐related contaminants which could prove challenging to remove during the high resolution purification steps. This paper addresses the use of microwell‐based ultra scale‐down (USD) methods to develop a bioprocess strategy focused on the integration of cell culture and cell removal operations and where the focus is on the use of operations which impart low shear stress levels even when applied at eventual manufacturing scale. An USD shear device was used to demonstrate that cells exposed to high process stresses such as those that occur in the feed zone of a continuous non‐hermetic centrifuge resulted in the reduction of the fusion protein and also the release of glycosylated intracellular variants. In addition, extended cell culture resulted in release of such variants. USD mimics of low shear stress, hydrohermetic feed zone centrifugation and of depth filtration were used to demonstrate little to no release during recovery of these variants with both results verified at pilot scale. Furthermore, the USD studies were used to predict removal of contaminants such as lipids, nucleic acids, and cell debris with, for example, depth filtration delivering greater removal than for centrifugation but a small (∼10%) decrease in yield of the fusion protein. These USD observations of product recovery and carryover of contaminants were also confirmed at pilot scale as was also the capacity or throughput achievable for continuous centrifugation or for depth filtration. The advantages are discussed of operating a lower yield cell culture and a low shear stress recovery process in return for a considerably less challenging purification demand. Biotechnol. Bioeng. 2013; 110: 1973–1983. © 2013 Wiley Periodicals, Inc.